PENGUKURAN NILAI KREATININ SERUM SEBELUM DAN SESUDAH TERAPI ANTIBIOTIK PADA PENDERITA INFEKSI GINJAL AKUT - Ika Christina; Muhammad Sungging Pradana; Evy Ratnasari Ekawati (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2022)
Urinary Tract Infection (UTI) is an infection due to the presence of microorganisms in the urine and has the potential to invade the tissues of the urinary tract. Urinary Tract Infection (UTI) depends on many factors such as age, gender, prevalence of bacteriuria and predisposing factors that cause changes in the structure of the urinary tract including the kidneys. Antibiotics are chemical substances produced by microorganisms that have the ability in aqueous solutions to inhibit the growth or kill microorganisms, for example penicillins, cephalosporins, chloramphenicol, tetracycline, and others. Creatinine is the end product of muscle creatine and creatine phosphate metabolism, synthesized in the liver, found in skeletal muscle, blood, and excreted in the urine. Creatinine levels are determined by the amount of muscle mass (the rate of protein catabolism). The type of research used is pre-experimental research with pre-test and post-test group design. In this design, observations were made twice, namely before the experiment was called the pre-test and after the experiment was called the post-test. A total of 30 patient samples, namely the serum creatinine value in the medium category has a value range of 4.9 - 6.9 mg/dl as many as 13 people with a percentage of 43.3%, and the serum creatinine value in the high category has a value range of 7.0 - 10 0.0 mg/dl as many as 17 people with a percentage of 56.7% it can be seen that the serum creatinine value in patients before antibiotic therapy has a range of values in the medium and high categories and after antibiotic treatment is given in the post test table, the serum creatinine value with the medium category has a value range of 4.9 – 6.9 mg/dl as many as 2 people with a percentage of 6.6%, and serum creatinine values in the low category have a value range of 1.1 – 4.8 mg/dl as many as 28 people with a percentage 93.4%. Keywords : Antibiotics, Creatinine